Charge transfer tuning in TiO2 hybrid nanostructures with acceptor–acceptor systems. Issue 9 (20th February 2017) - Pilarczyk, K.; Lewandowska, K.; Mech, K.; Kawa, M.; Gajewska, M.; Barszcz, B.; Bogucki, A.; Podborska, A.; Szaciłowski, K.
Abstract : The interplay between titanium dioxide and two electron acceptors (graphene oxide and chloranilic acid) results in the fine-tuning of photoelectrochemical properties of the ternary nanocomposite. Abstract : An interesting interplay between two different modifiers and the surface of titanium dioxide leads to a significant change in the photoelectrochemical properties of the designed hybrid materials. The semiconductor is photosensitized by one of the counterparts and exhibits the photoelectrochemical photocurrent switching effect due to interactions with graphene oxide – the second modifier mediates charge transfer processes in the system, allowing us to design the materials response at the molecular level. Based on the selection of molecular counterpart we may affect the behaviour of hybrids upon light irradiation in a different manner, which may be useful for the applications in photovoltaics, optoelectronics and photocatalysis. Here we focus particularly on the nanocomposites made of titanium dioxide with graphene oxide combined with either 2, 3, 5, 6-tetrachlorobenzoquinone or 2, 3-dichloro-5, 6-dihydroxybenzoquinone – for these two materials we observed a major change in the charge transfer processes occurring in the system.